Accountability and transparency: Police forces in England and Wales. (July 2017) - Murphy, Peter; Eckersley, Peter; Ferry, Laurence
Between 2010 and 2015, the UK's Coalition Government introduced directly-elected Police and Crime Commissioners to oversee English and Welsh police forces, and also required every force to publish a range of performance and financial information online. Together with the fact that front-line policing services have not been outsourced or privatised, this suggests that strong 'downwards' mechanisms exist through which residents can hold their local force to account. However, the new arrangements are significantly more complex than their predecessors, because many more actors are involved – several of which assume the role of both 'principal' and 'agent' in different accountability relationships. As a result, there is a substantial risk that the public do not have a clear understanding of roles and responsibilities, which makes it more difficult to hold officials to account for their actions. Such findings highlight how direct elections do not necessarily make public officials more accountable, and therefore have implications for other jurisdictions and sectors.